2015
DOI: 10.1039/c5dt00159e
|View full text |Cite
|
Sign up to set email alerts
|

Spirocyclic, macrocyclic and ladder complexes of coinage metals and mercury with dichalcogeno P2N2-supported anions

Abstract: Reactions of the dianions [tBuN(E)P(μ-NtBu)]22− (E = Se,S) with M(i) reagents (M = Ag, Au) or HgCl2 produce complexes of [tBu(H)N(E)P(μ-NtBu)2P(E)NtBu]− with spirocyclic, macrocyclic or ladder structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 40 publications
0
6
1
Order By: Relevance
“…As in the previous work with L 2– (E = Te), E,E′-chelated complexes were the major products for selenium, but the N,S-chelated isomers predominated for the sulfur systems. The formation of Se,Se′-chelated complexes with p-block elements contrasts with our recent studies of coinage metal complexes in which attempted metathetical reactions of L 2– (E = Se) with silver­(I) or gold­(I) halides produces macrocycles that incorporate the monoprotonated ligand H L – …”
Section: Discussioncontrasting
confidence: 66%
“…As in the previous work with L 2– (E = Te), E,E′-chelated complexes were the major products for selenium, but the N,S-chelated isomers predominated for the sulfur systems. The formation of Se,Se′-chelated complexes with p-block elements contrasts with our recent studies of coinage metal complexes in which attempted metathetical reactions of L 2– (E = Se) with silver­(I) or gold­(I) halides produces macrocycles that incorporate the monoprotonated ligand H L – …”
Section: Discussioncontrasting
confidence: 66%
“…10 %) . A recently developed approach involves the incoporation of the well established building block [ t BuN=(E)P(μ‐N t Bu)] 2 2− . Oxidation with elemental iodine yields the (‐E‐E‐) bridged trimeric macrocycle [( t BuN=)P(μ‐N t Bu) 2 (μ‐E 2 )] 3 ( E , Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, late transition metal complexes of ansa‐bridged dicyclophosphazanes B (Figure 1), in which chirality can be introduced at the diol bridge and/or at the amido R group, have allowed the observation of match and mismatch effects in enantioselective catalysis, with good enantiomeric excesses being found for the gold‐catalysed hydroamination of γ‐allenyl sulfonamides and the asymmetric nickel‐catalysed three‐component coupling of a diene and an aldehyde [20] . Another key area of interest has been the coordination chemistry of a range of valance‐isoelectronic phosph(III)azane (C, Figure 1) and phosph(V)azane dianions (D and E, Figure 1), particularly in regard to the large number of donor atoms available for metal coordination and the resulting wealth of metal coordination modes observed [7, 21–25] …”
Section: Introductionmentioning
confidence: 99%
“…[20] Anotherk ey area of interest has been the coordinationc hemistry of ar ange of valance-isoelectronicp hosph(III)azane (C, Figure 1) and phosph(V)azane dianions (D and E, Figure 1), particularly in regard to the large number of donora toms available for metal coordination and the resulting wealth of metal coordination modes observed. [7,[21][22][23][24][25] In addition to applicationsa sm etal donor ligands, phosphazane frameworks have recently also formed the basis for a number of H-bonding anion receptor molecules.T hese include simple systems based on dicyclophosph(III)azanes, of the general type [RNHP(m-NR)] 2 ,a nd more elaborate phosphazane macrocycles, like the pentamer [{P(m-N t Bu)} 2 (NH)] 5 . [12,13,26,27] Our recent studies of the modela nion receptor[ (2-py)NHP(m-N t Bu)] 2 (1), showed that the P, N-chelationo ft ransition metals has three important effects, stabilising the P 2 N 2 framework so that it becomes air-and moisture-stable,p re-organising the N-HH -bonding functionality foro ptimum H-bonding to anions, and dramatically increasingt he polarisation of the NÀHb onds ( Figure 2).…”
Section: Introductionmentioning
confidence: 99%